Sb‐Doped SnO2 Nanorods Underlayer Effect to the α‐Fe2O3 Nanorods Sheathed with TiO2 for Enhanced Photoelectrochemical Water Splitting. Issue 19 (14th April 2018) - Han, Hyungkyu; Kment, Stepan; Karlicky, Frantisek; Wang, Lei; Naldoni, Alberto; Schmuki, Patrik; Zboril, Radek
Abstract: Here, a Sb‐doped SnO2 (ATO) nanorod underneath an α‐Fe2 O3 nanorod sheathed with TiO2 for photoelectrochemical (PEC) water splitting is reported. The experimental results, corroborated with theoretical analysis, demonstrate that the ATO nanorod underlayer effect on the α‐Fe2 O3 nanorod sheathed with TiO2 enhances the PEC water splitting performance. The growth of the well‐defined ATO nanorods is reported as a conductive underlayer to improve α‐Fe2 O3 PEC water oxidation performance. The α‐Fe2 O3 nanorods grown on the ATO nanorods exhibit improved performance for PEC water oxidation compared to α‐Fe2 O3 grown on flat fluorine‐doped tin oxide glass. Furthermore, a simple and facile TiCl4 chemical treatment further introduces TiO2 passivation layer formation on the α‐Fe2 O3 to reduce surface recombination. As a result, these unique nanostructures show dramatically improved photocurrent density (139% higher than that of the pure hematite nanorods). Abstract : An antimony‐doped tin oxide nanorod underlayer is designed and synthesized by aqueous thermal hydrolysis and subsequent Sb‐doping . The experimental results, corroborated with theoretical analysis demonstrate that the antimony‐doped tin oxide nanorod underneath effect on the α‐Fe2 O3 nanorod sheathed with TiO2 plays an important role in enhancing the photoelectrochemical water splitting performance.